Combined Effect of Vitamin D Supplementation and Physiotherapy on Reducing Pain Among Adult Patients With Musculoskeletal Disorders: A Quasi-Experimental Clinical Trial - Ali, Mohammad; Uddin, Zakir; Hossain, Ahmed (Frontiers in Nutrition, 2021)
Background: The prevalence of musculoskeletal disorders (MSD) and vitamin D insufficiency is high. Past research indicating vitamin D supplementation and physiotherapy are useful for the treatment of MSDs. However, to the best of our knowledge, the combined benefits of vitamin D and physiotherapy are not yet evaluated in MSD. We hypothesized that combined intervention of vitamin D supplementation and physiotherapy would be more effective in relieving the pain of MSD compared to only physiotherapy intervention. Objective: This study aimed to examine whether combined effect of vitamin D supplementation and physiotherapy was better than physiotherapy alone in reducing pain-related outcomes (e.g. pain severity, affective interference, and physical interference) in patients with MSD. Methods: A quasi-clinical experiment was conducted between May 2020 and April 2021. Vitamin D level in the blood was measured at the start of the study. Patients with vitamin D levels less than 20 ng/mL were assigned to the combined physiotherapy and vitamin D group. The physiotherapy group consisted of the patients with vitamin D levels more than 20 ng/mL. The Brief Pain Inventory scale was utilized to measure pain at baseline and after 12 weeks of interventions. We used the paired t-tests for unadjusted analysis. Further, a linear regression model was used to identify the combined effect of physiotherapy and vitamin D on reducing pain scores after adjusting potential confounders. Results: Combined intervention of vitamin D and physiotherapy showed significantly better results than only physiotherapy intervention in the reduction of three pain-related outcomes (p < 0.001). The multivariable analysis indicated that the combination of physiotherapy and vitamin D treatment reduced pain score by 1.126 (slope = -1.126, p = 0.035) compared to physiotherapy alone. Conclusion: Combined intervention (vitamin D with physiotherapy) had a better pain-relieving effect than physiotherapy alone. To confirm these findings, more research is needed with randomized control trials. Clinical Trial registration: CTRI/2020/04/024845, Registered on 24/04/2020, http://ctri.nic.in/Clinicaltrials/advancesearchmain.php